Analisis Strategi Keunggulan Kompetitif Berkelanjutan Perusahaan Crowd Business Syariah (Studi Kasus pada Halal Network International) - Amirah Firas Mufidah; Laily Dwi Arsyianti; Ibdalsyah (AL-MUZARA'AH, 2021)
Business model innovation of a company is a form of adaptation to the current economic turmoil to determine competitive advantage. To deal with this, PT HPA Indonesia or Halal Network International (HNI) which is based on the Muslim crowd and consistently is considered to be developing and getting the leading position must be able to survive in the middle of challenging market. The purpose of this research is to analyze the strategy of sustainable competitive advantage for HNI as sharia crowd business firm. The mixed method approach was carried out using literature studies, guided interviews, and online questionnaires for certain experts. The data processing technique used in this research is ANP (Analytical Network Process) to involve the analysis of the relationship between the network elements. The results of this research indicate that effective strategy is the right strategy for sustainable competitive performance. This strategy focuses on developing resource capital. The three elements with the lowest priority in this pride strategy model are reputation & quality control, technology & buyer fulfillment and sales of product content. By combining institutional capital and resource capital, a sustainable competitive advantage can be achieved by focusing performance on the subfactors of corporate image and leadership.